SAND DIAGENESIS ROCK PHYSICS MODEL TO PREDICT MECHANICAL PROPERTIES OF SUBSURFACE ROCK IN ORDER TO IDENTIFY SANDING PROBLEM. - Harisandi, Azhar
Sand production problem is a phenomenon in a geologically young producing reservoir -hence relatively low compaction effect and rock strengthwhere solid grains from reservoir transported within the production fluids because the rock itself cannot withstand the pressure that is applied to produce the reservoir. When sanding initially occurs, part of the producing reservoir behaves like a suspended sediment phase, which can only exist above critical porosity point. In this state, any stress or pressure applied to the material will be distributed uniformly by the fluid phase. Rock physics model, specifically sand diagenesis model was made to create a solid fundamental in describing effective elasticity in this field. The model shows a good agreement with the data because it accommodates change in trend of increasing elastic moduli with decrease in porosity in lower porosity range, which turns out that in this range, the dominant mechanism of compaction is chemical compaction or cementation instead of mechanical compaction. Modeled Vp from this model is used to establish empirical relation of porosity and rock strength with laboratory rock mechanical testing data as a calibration points. From rock mechanical testing data applied to three arenite core sample, it is observed that decrease in UCS is accompanied by increase in Poisson’s ratio that can be viewed as a process similar to liquefaction in initial stage of sanding instead of brittle failure, where a part of the rock loses its grain and the suspended grains behave like fluids. From this observation, critical porosity point is assumed to be the state where initial sanding occurs. If the rock strength in the critical porosity point can be estimated, then it is possible to predict the maximum amount of pressure that can be applied to prevent sanding.